(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Background: Helminthiasis is a common health problem in children globally specially in developing countries. Children at school age are more prone to develop such problems specifically when they are exposed to lower socioeconomic status, poor hygienic standards and environmental factors suitable for helminthic development. Objective: To determine possible positive cases of intestinal parasitic infection among primary school children. Study Design: A descriptive cross sectional study. Place and Duration of Study: Study was conducted in four schools, two for boys and two for girls in Allama Iqbal Town, Lahore from 15th January 2010 to 15th April 2010. Materials and Methods: The study population included 400 primary school children of grade 1 to 5 of both sexes. Stool examination was done at Medical Entomology and Parasitology Laboratory, Institute of Public Health, Lahore on three consecutive days of a week The results obtained were analyzed using SPSS 15. Results: Amongst 400 stool specimens examined of primary school children, 194 (48.5%) were found positive for various intestinal helminthes. Six different types of helminthes were identified. The commonest species found was Ascaris lumbricoides, 33.25% whereas H. nana,6.25%, A. duodenale 2% , E. vermicularis 2.25%, T. trichiura 2.75% and T. saginata 2% were detected. No mixed infection was found. Conclusion: This study revealed that helminthiasis is a significant health problem among studied primary school children of Allama Iqbal Town, Lahore.